Inspiratory muscle capacity with abdominal support: a prospective observational study in critically ill patients - Mól, Caroline Gomes (2022)
Background: Critically ill patients are at risk of many complications related to critical illness and ICU length of stay, as respiratory muscles dysfunction and lung aeration loss. Therefore, we constructed two different research questions: can abdominal support influence the inspiratory muscles capacity in critically ill patients in spontaneous breathing? Is there any relationship between diaphragm excursion (DE), inspiratory muscle strength and lung aeration in critically ill patients? Aims: Our main purpose is to investigate the inspiratory muscle capacity in critically ill patients with and without abdominal support. Secondary aims were also proposed to answer research question 2: to investigate the relationship between lung aeration, DE and maximal inspiratory pressure (MIP); to investigate if the diaphragm motion dysfunction assessed by ultrasound could be predicted from the patient\'s clinical characteristics. Methods: Adults admitted to the intensive care unit (ICU) for at least 48 hours and breathing spontaneously were included. To answer research question 1, patients were assessed during three different breathing patterns as follows: tidal breathing (1); maximal inspiratory effort without abdominal support (2) and maximal inspiratory effort with abdominal support (3). During the breathing pattern (3), a standardized 10mmHg-belly belt was positioned to promote abdominal support. For the pattern (2), the belt was positioned without any tension. For the patterns (2) and (3), the assessments were performed during a maximal inspiratory effort emphasizing the abdominal outward displacement during inspiration. Outcome measures included lung ultrasound score (LUS), maximal inspiratory pressure (MIP), vital capacity (VC), diaphragm excursion (DE) and diaphragm thickening fraction (TFdi). Within the thirty patients included, 24 had MIP and DE during a maximal inspiratory effort assessed at the baseline moment, during breathing pattern 1, which enabled the analysis proposed in research question 2. Results: Thirty critically ill patients were assessed. Maximal inspiratory pressure during the breathing pattern (3) was significantly higher than in the pattern (2). All comparisons of DE between the three breathing patterns showed significant differences [DE (3)>(2)>(1)]. Considering TFdi, there was a significant difference between the patterns (2) and (3) [TFdi (3)>(2)=(1)]. There was a highly significant (p 0.001) relationship between deep breathing diaphragm excursion and LUS of dependent lung regions (r = - 0.772) and total LUS (r = - 0.651). The area under the curve of DDRS for prediction of diaphragm dysfunction was 0.759: A DDRS 2 had a sensitivity of 81.8% and a specificity of 61.5%. Conclusion: Abdominal support improves MIP, DE and TFdi of critically ill patients in spontaneous breathing when compared to the pattern without abdominal support. Additionally, diaphragm dysfunction contributes to lung aeration loss, especially in dependent lung areas. A DDRS 2 is predictive of diaphragm dysfunction